Identification and bioinformatics analysis of a novel member of the lumbrokinase gene family in earthworms - Rongchuan, Xiong; Jianhong, Li; Tingchang, Liu; Chengyuan, Su; Hong, Chen; Zhengpeng, Chen; Chaozhi, Tang; Xinxia, Zhao (Frontiers in Bioinformatics, 2026)
BackgroundLumbrokinase is a novel antithrombotic drug isolated and purified from earthworms and used in the treatment of stroke and cardiovascular disease. However, to date, there has been no systematic classification of lumbrokinase genes.MethodsIn this study, a new member of the lumbrokinase gene family LUKA, which has not yet been reported, was cloned from Eisenia andrei by a homologous sequence method. The full-length cDNA sequence of LUKA was obtained through second-generation sequencing. The gene and protein were analyzed using various bioinformatics software tools.ResultsThe molecular formula of LUKA was C1347H2068N360O419S18, indicating it is a stable protein. The amino acid sequence of LUKA contained high proportion of valine (10.2%) and serine (9.2%) and possessed a peptide signal along with the corresponding cleavage site.ConclusionPhylogenetic analysis showed that LUKA has multiple distinct amino acid sites compared with other lumbrokinases and represents a rare type of lumbrokinase. This study provides a new genetic material of rare lumbrokinase types.